(untitled) (Research in Agriculture Livestock and Fisheries, 2018)
An experiment was conducted to prepare anti-Aeromonas hydrophila serum in two rabbits (Oryctolagus cuniculus). Formalin killed cell (FKC) and heat killed cell (HKC) were prepared by adding 0.5% formalin and 2.5 h heat treatment at 60°C of freshly cultured Aeromonas hydrophila (AQC810) isolated from naturally infected koi fish kidney respectively. Slide agglutination tests were performed for the determination of the presence of specific antibody against Aeromonas hydrophila in the serum collected from the blood of pre-immune rabbits or post immune rabbits. No agglutination of pre-immune serum with the homologous antigen proved that the rabbits had no previous Aeromonas contamination. Rabbits were injected subcutaneously with the FKC added with same amount of Freund’s complete adjuvant. Three booster doses were given without the adjuvant at weekly intervals after second week of first injection. Agglutination titration of anti-Aeromonas hydrophila rabbit serum against HKC and FKC of homologous bacteria showed that the titers increased with the post inoculation days which rose at their peak during the fifth week of immunization and after three consecutive booster doses at weekly intervals starting from second week of first immunization. Rabbits were sacrificed after six weeks of immunization, whole blood, collected and centrifuged to accumulate the serum that were complementinactivated by heating to 58ºC for 30 min and stored at -20°C in appendorph tubes, with the aim of rapid diagnosis of Aeromonas infections in fishes. Result of this study would initiate the way of vaccine development against MAS (motile Aeromonas septicemia) in the aquaculture fishes of Bangladesh. Res. Agric., Livest. Fish.5(1): 137-145, April 2018